2017
DOI: 10.1038/srep40513
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Microvascular Changes in the Retina following Kawasaki Disease

Abstract: It is unclear whether all children with Kawasaki disease (KD) have increased later cardiovascular risk. The retinal microvasculature reflects changes in the microcirculation and is associated with traditional cardiovascular risk factors and events. The aim of this study was to investigate retinal microvascular parameters in two populations of patients with previous KD and control participants. We performed case-control studies of 116 (57 patients and 59 control participants) Australian and 156 (78 patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…A previous study found that increment of coronary artery diameters was associated with wider retinal venules in paediatric KD patients with recurrent acute flares 5 . We found however, that retinal arteriolar changes, instead of retinal venular changes, were associated with coronary artery changes during the acute phase of new KD onset.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…A previous study found that increment of coronary artery diameters was associated with wider retinal venules in paediatric KD patients with recurrent acute flares 5 . We found however, that retinal arteriolar changes, instead of retinal venular changes, were associated with coronary artery changes during the acute phase of new KD onset.…”
Section: Discussionmentioning
confidence: 88%
“…Both geometric parameters reflect an optimal blood circulation in the retina. Thus, altered fractal dimension and/or curvature tortuosity could reflect increased angiogenesis or oxidative stress in response to inflammatory-induced neuro-retinal hypoxia and endothelial dysfunction 5 . Although increased retinal tortuosity has been speculated to be related to increased blood flow and angiogenesis 1315 , the true physiologic significance of increased retinal arteriolar tortuosity is still not fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes may serve as key players in the pathophysiology of vascular damage outside cardiovascular system. 23 Although the number of children reported to present this complication is small and does not permit the identification of more risk factors, literature data imply that an early diagnosis and initiation of appropriate treatment prevent the appearance of this complication. 16…”
Section: Strokes Ischemic Strokesmentioning
confidence: 99%
“…Recently, Chen et al . reported that the retinal venules of patients with KD at least 2 years after acute illness were larger in size than those of control participants after adjusting for traditional cardiovascular risk factors . Furthermore, an increase in the size of retinal venules was observed in patients with coronary artery abnormalities compared with control patients.…”
mentioning
confidence: 96%